A garland of bones : child runaways in India - Steinberg, Jonah (Yale agrarian studies., 2019)
An intimate portrait of India's child runaways, and the sociopolitical forces shaping their lives This intimate portrait examines the tracks, journeys, and experiences of child runaways in northern India. Jonah Steinberg situates children's decisions to leave home and flee for the city in their larger cultural, social, and historical contexts, and considers histories of landlessness and debt servitude in narratives of child dislocation. The resulting work is an original perspective on the sociological trends in postcolonial India and a unique treatment of a population of individuals who live on the margin of society.